تعبير القصة في تعليم قصة بلال بن رابة لتنمية مهارة الكلام - Taufik, Taufik; Syafi'i, Imam; Hadi, Junaidil; Rosidi, Muhammad Farhan (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
In this study, the researchers found several problems which in general include the lack of precise learning methods, unfulfilled learning facilities, and the lack of students in mastering speaking skills in Arabic. This study aims to determine how effective the application of story telling in learning the story of Bilal bin Rabah is to develop the speaking skills. The use of the story telling learning method in Bilal bin Raba's story is one of the tools used in the learning process to improve and develop speaking skills in Arabic.